1997
DOI: 10.2466/pms.1997.84.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Respiratory Sinus Arrhythmia and Heart-Rate Responses during Auditory Stimulation of Children with Attention-Deficit Hyperactivity Disorder

Abstract: During passive and active listening tasks baseline respiratory sinus arrhythmia and heart-rate responses were studied of 18 children with Attention-Deficit Hyperactivity Disorder (ADHD) and 49 healthy school children. The experimental procedure included baseline recording (no task), a passive listening task, instructions, and both simple and discriminative active-listening tasks. ADHD subjects showed less respiratory sinus arrhythmia than normal children but were similarly responsive to tone stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
2
9
2
Order By: Relevance
“…An increase in LF/HF ratio signifies that there was sympathovagal imbalance with sympathetic dominance [13] . Similar results were obtained in studies carried out by Shibagaki and Furuya [19] and Beauchaine et al [20] . In the study carried out by Shibagaki and Furuya [19] , high frequency component of HRV was reduced in children with ADHD as compared to controls during baseline and listening tasks.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…An increase in LF/HF ratio signifies that there was sympathovagal imbalance with sympathetic dominance [13] . Similar results were obtained in studies carried out by Shibagaki and Furuya [19] and Beauchaine et al [20] . In the study carried out by Shibagaki and Furuya [19] , high frequency component of HRV was reduced in children with ADHD as compared to controls during baseline and listening tasks.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were obtained in studies carried out by Shibagaki and Furuya [19] and Beauchaine et al [20] . In the study carried out by Shibagaki and Furuya [19] , high frequency component of HRV was reduced in children with ADHD as compared to controls during baseline and listening tasks. In the study carried out by Beauchaine et al [20] , high frequency component of HRV was significantly lower in ADHD/conduct disorder group compared to ADHD and control group during baseline.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is therefore very interesting to note that children with ADHD, who are generally more impulsive and aggressive than controls, have been found to have a lower resting HR than control subjects. These results do not support the parasympathetic nervous system findings from Crowell et al [24] , which indicate that stimulant-free children with ADHD do not differ from agematched controls with regard to parasympathetic nervous system activity, or the results of Shibagaki and Furuya [39] , which suggest that children with ADHD display an underactivity of the parasympathetic nervous system when compared to controls. A possible reason for the difference in findings from those of Crowell et al [24] could be that Crowell et al simply looked at the HF component of HRV as a measure of parasympathetic nervous system activity in their patients.…”
Section: Baseline Autonomic Nervous System Activitycontrasting
confidence: 56%
“…In addition, very little is known about parasympathetic nervous system functioning in ADHD. While Crowell et al [24] found that children with ADHD do not differ from control subjects with regard to parasympathetic nervous system activity, results from the study by Shibagaki and Furuya [39] suggest that children with ADHD display a level of parasympathetic underarousal. What is overlooked is the fact that the functional outcome is dependent on the autonomic balance, rather than merely sympathetic or parasympathetic activation.…”
Section: Discussionmentioning
confidence: 73%